2014
DOI: 10.1007/s00464-014-3504-z
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the latency effects on surgical performance and the acceptable latency levels in telesurgery using the dV-Trainer® simulator

Abstract: The surgical performance deteriorates in an exponential way as the latency increases. The delay impact on instrument manipulation is mild at 0-200 ms, then increases from small to large at 300-700 ms, and finally becomes very large at 800-1,000 ms. Latencies ≤200 ms are ideal for telesurgery; 300 ms is also suitable; 400-500 ms may be acceptable but are already tiring; and 600-700 ms are difficult to deal with and only acceptable for low risk and simple procedures. Surgery is quite difficult at 800-1,000 ms, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(89 citation statements)
references
References 22 publications
4
79
1
1
Order By: Relevance
“…For example, Kumcu et al 30 reported deterioration in the performance and user experience beyond a 105-ms system latency. Xu et al 31 claimed that the impact of latency on instrument manipulations was mild in the 0 to 200-ms range and that a less than 200-ms latency was ideal for telesurgery. Perez et al 32 reported a measurable deterioration in the performance beginning at a latency of 300 ms. Based on these results, our measured system latency is within a clinically acceptable range.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Kumcu et al 30 reported deterioration in the performance and user experience beyond a 105-ms system latency. Xu et al 31 claimed that the impact of latency on instrument manipulations was mild in the 0 to 200-ms range and that a less than 200-ms latency was ideal for telesurgery. Perez et al 32 reported a measurable deterioration in the performance beginning at a latency of 300 ms. Based on these results, our measured system latency is within a clinically acceptable range.…”
Section: Discussionmentioning
confidence: 99%
“…After informed consent had been obtained, the subjects were randomly split into two groups: the 400 ms delay group (G400; n = 5) and the 600 ms delay group (G600; n = 6). In the previous study, we demonstrated that 400-500 ms and 600-700 ms have a moderate and large impact, respectively, on instrument manipulation; training at these two latency levels would be representative (8).…”
Section: Methodsmentioning
confidence: 97%
“…Remote surgeons may be confronted with considerable time delay (500-900 ms) in the absence of dedicated fibre-optic lines (4)(5)(6)(7). We demonstrated in a previous study that simple telesurgical procedures remain possible with a delay up to 700 ms (8). However, the surgical performance deteriorates gradually as latency increases (8)(9)(10).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…"Telesurgery" has since been an active area of technological research and development. Recent trials have attempted to assess the effect of communication latency on surgical performance [22][23][24], expand the scope of procedures achievable through telesurgery [24,25] and improve haptic feedback relayed to remote operators [26]. However, at present, telesurgery requires acquisition and maintenance of a robotic platform that is likely to be prohibitively expensive for rural treatment sites [27].…”
Section: Surgery and Postoperative Carementioning
confidence: 98%